Bio-optical properties of the subtropical North Atlantic. I. Vertical variability - Bouman, H; Platt, T; Kraay, G; Sathyendranath, S; Irwin, B (2000)
Studies of the physiological and optical properties of phytoplankton of the subtropical open ocean are rare. Yet, assessing the spatial and temporal variation in the photo-physiological parameters and chlorophyll-specific absorption coefficients of marine phytoplankton is essential if we are to account for the relative importance of pelagic systems in the global carbon economy. As a contribution to this general goal, the photosynthetic and bio-optical properties of phytoplankton were measured at 5 stations across a broad swath of the subtropical North Atlantic Ocean. Similar vertical patterns in pigment composition, chlorophyll-specific absorption coefficients and the photosynthesis-irradiance parameters were observed at all 5 stations. A considerable proportion of the vertical variation in the chlorophyll-specific absorption coefficients was caused by vertical changes in the proportion of the non-photosynthetic pigment (NPP) zeaxanthin relative to chlorophyll a. On the other hand, pigment packaging appeared to have a minor influence on the optical characteristics of the picoplankton-dominated region: chlorophyll-specific absorption coefficients observed at the red peak frequently exceeded 0.02 m2 (mg chl a)-1. Multiple, linear-regression analysis was used to examine the value of some commonly-measured environmental variables as potential predictors of the photosynthetic parameters αB and PmB. The results showed that indices of ambient irradiance, nutrient flux or nutrient concentration, separately or in combination, account for a significant fraction of the total variance in the photosynthetic parameters. The stability in the distribution patterns of both the photosynthetic parameters and absorptive characteristics of subtropical phytoplankton assemblages and in the principal factors governing the variability in these properties may facilitate the selection of appropriate input parameters for use in models of primary production for this hydrographic region.